The management of urolithiasis. Issue 7 (July 2019) - Arumuham, Vimoshan; Brodie, Andrew; Bycroft, John
Abstract: The incidence and prevalence of urolithiasis is on the rise; though inevitably the increasing availability of cross-sectional imaging has some contribution to this rise in diagnoses, it cannot take all the blame. Urolithiasis is now more commonly being recognized as a symptom of a more systemic disease which has a constellation of presenting signs and complaints. The authors aim to outline the precipitating causes of urolithiasis, along with a comprehensive discussion of the current operative trends available to the practising endourologist. Despite largely being tailored to trainees within Core Training, in parts the discussion will head beyond that what is expected during basic surgical training and move into topics of debate within higher specialist training.